Environmental transformation and nano-toxicity of engineered nano-particles (ENPs) in aquatic and terrestrial organisms. Issue 23 (1st December 2020) - Abbas, Qumber; Yousaf, Balal; Ullah, Habib; Ali, Muhammad Ubaid; Ok, Yong Sik; Rinklebe, Jörg
Abstract: The rapid development in nanotechnology and incorporation of engineered nano-particles (ENPs) in a wide range of consumer products releasing the massive quantities of ENPs in different environmental compartments. The released ENPs from nano-enabled products during their life cycle raising environmental health and safety issues. This review addresses the recent state of knowledge regarding the ENPs ecotoxicity to various organisms lying at different trophic levels. Studies show that reactive oxygen species (ROS) mediated oxidative stress is the primary mechanism of nano-toxicity, either through physical damage by direct contact or release of toxic ions after ENPs dissolution process. Moreover, ENPs uptake, transformation and toxicity on physio-morphological, biochemical and molecular levels in primary producers of terrestrial environment (plants) were also reviewed. Additionally, the intrinsic detoxification mechanism in plants in response to ENPs accumulation was also examined. In the end different sustainable approaches such as biogenic synthesis, clay minerals role, biochar application, bioremediation, and legislative measures are proposed for effective handling and treatment of nano-wastes to get the maximum benefits of nanotechnology with minimum negative outcomes. Graphical Abstract: